THE COMPARISON OF EFFICACY BETWEEN LOSARTAN AND DILTIAZEM AS ANTIPROTEINURIC AGENT IN NON-DIABETIC RENAL DISEASES - Salahuddin; Malik Nadeem Azam; Khalid Mehmood Raja; Abdur Rehman Arshad; Faryal Riaz Khan; Abdul Wahab Mir; Taleha Tahir; Batool Butt; Wahaj; Anum Khan (Journal of Ayub Medical College Abbottabad, 2021)
Background: Multiple options have been tried to counter the proteinuria secondary to renal diseases. Clinicians and researchers are trying to find the best option for this purpose. Objective: To compare efficacy of Losartan and Diltiazem in management of proteinuria in non-diabetic renal diseases at a tertiary care hospital of Pakistan. It was a Quasi-experimental study, conducted at the Department of nephrology Pak Emirates Military Hospital Rawalpindi. Five months, November 2020 to March 2021. Methods: A total of 122 patients of non-diabetic renal diseases with significant proteinuria were included in the study. They were randomly divided into two groups via lottery method. Group I received losartan while group II received Diltiazem in standard dose for three months. After three months they underwent 24 hours’ urinary protein levels and divided into complete, partial and non-responders to treatment. Age, gender, duration of illness and type of antiproteinuric treatment was correlated with response to treatment among the study population. Results: Out of 122 patients, 80 (65.6%) were males while 42 (34.4%) were females. Membranous nephropathy 20 (16.4%) was the commonest non-diabetic renal disease seen in our study participants. Thirty (24.5%) had complete remission after three months of treatment, 60 (49.2%) had partial response while 32 (26.3%) had no response to treatment. Chi-square test revealed that use of losartan had statistically significant relationship (p-value<0.001) with good response among the study participants. CONCLUSION: Membranous nephropathy leading to proteinuria was the commonest non-diabetic renal disease encountered in our setup. Around 2/3rd of our patients showed either complete or partial response to treatment and Losartan was superior to Diltiazem in achieving response in our study participants.